In Our Time - Tao Te-chen; Yang, Edward; Ko I-chen; Chang Yi; Chen Chia-mao; Chang, Emily Y.; Chang, Sylvia; Chen Chi (Taiwan New Wave Cinema, 2015)
Four stories, filmed by four different directors, all newcomers and mostly trained in film schools abroad where they picked up new ideas about cinema quite divergent from those of their Taiwanese elders. Each story is set in a different decade, moving forward chronologically (1950s, ’60s, ’70s, ’80s) and with protagonists of increasing ages as time goes on (a boy of about 8, a young teenage girl, a university student, a married couple moving into their own flat for the first time). Thus goes the basic premise of "In Our Time", but as with all omnibus films, not all parts are as strong as the others. In this case, the first two episodes are the most impressive and satisfying. [cine-scope.com]